Intimate partner violence and women's economic preferences - Anderberg, Dan; Cassidy, Rachel; Dam, Anaya; Hidrobo, Melissa; Leight, Jessica; Morsink, Karlijn (arXivLabs, 2025)
One in three women globally experiences intimate partner violence (IPV), yet little is known about how such trauma affects economic decision-making. We provide causal evidence that IPV influences women's time preferences - a key parameter in models of savings, investment, and labor supply. We combine two empirical strategies using four distinct datasets. First, in two randomized recall experiments in Ethiopia, we randomly assigned women to recall specific acts of abuse before eliciting their intertemporal choices. Women with IPV experiences prompted to recall IPV display significantly greater impatience than otherwise similar women who are not prompted. Second, we exploit exogenous reductions in IPV generated by two randomized interventions - one involving cash transfers, the other psychotherapy - and use treatment assignment as an instrument for IPV exposure. Women who experience reduced IPV as a result of treatment exhibit more patient time preferences. Together, these results provide consistent, novel causal evidence that exposure to IPV induces individuals to discount the future more heavily. This evidence suggests a psychological channel through which violence can perpetuate economic disadvantage and constrain women's ability to take actions - such as saving, investing, or exiting abusive relationships - that require planning over time.